South Pacific - Osborn, Paul, 1901-1988; Hammerstein, Oscar, II, 1895-1960; Adler, Buddy, 1906-1960; Logan, Joshua; Brazzi, Rossano, 1916-1994; Gaynor, Mitzi, 1931-; Kerr, John, 1931-2013; Walston, Ray, 1917-2001; Hall, Juanita, 1901-1968; Nuyen, France, 1939-; Rodgers, Richard, 1902-1979; Michener, James A. (James Albert), 1907-1997 ([CBS Fox Video], 1999)
Set in the Pacific theater during World War II, this musical film explores the theme of racial prejudice in two parallel stories--that of a Navy nurse's love for a plantation owner with two Eurasian children, and a Marine lieutenant's love for a native woman.